Partisipasi Masyarakat Mapadegat Dalam Pengembangan Pariwisata Di Obyek Wisata Pantai Mapadegat Kepulauan Mentawai - Saogo, Ardi; Oktavia, Dian Anggraini; Elfemi, Nilda (Pendidikan Sosiologi, 2013)
This study aimed to describe Mapadegat community participation in tourism development in coastal attractions Mapadegat Mentawai Islands. The theory used is a phenomenological theory. The research is descriptive qualitative study subjects were taken purposively sampling criteria are research subjects local government and some members of the public.And data collection techniques that are used are observation, interview and documentation, data collection tool used is the researchers themselves who go directly into the field, guide research and data, library books, and photos of cameras. Data analysis technique used is the data reduction, interpretation/display the data, and verification/making conclusions.Results of this study are as follows : (1) Public Mapadegat participate in maintaining the attitude to remain polite, friendly, polite and caring at every visitor who comes traveled on the beach attractions in Mapadegat. (2) Community Mapadegat participate in maintaining the infrastructure, security, cleanliness and order every visitor who comes traveled on the beach attractions in Mapadegat. (3) Community Mapadegat participate in the development of tourism through the construction of dams, wc, lodging and youth shelters in the coastal tourist attraction in Mapadegat. (4) Community Mapadegat participated in the land to allow the construction of tourism infrastructure in the coastal tourist attraction in Mapadegat. (5) participate in providing public transportation services tourists coming traveled on the beach attractions Mapadegat and recycling bins for used bags. (6) People ( tourists ) come and keep the attitude to not pollute and damage the infrastructure and Mapadegat beach cleanliness and dress modestly, sociable and well behaved